SARS-CoV-2 neutralizing antibody responses are more robust in patients with severe disease. Issue 1 (1st January 2020) - Wang, Pengfei; Liu, Lihong; Nair, Manoj S.; Yin, Michael T.; Luo, Yang; Wang, Qian; Yuan, Ting; Mori, Kanako; Solis, Axel Guzman; Yamashita, Masahiro; Garg, Ankur; Purpura, Lawrence J.; et al.
ABSTRACT: We studied plasma antibody responses of 35 patients about 1 month after SARS-CoV-2 infection. Titers of antibodies binding to the viral nucleocapsid and spike proteins were significantly higher in patients with severe disease. Likewise, mean antibody neutralization titers against SARS-CoV-2 pseudovirus and live virus were higher in the sicker patients, by ∼5-fold and ∼7-fold, respectively. These findings have important implications for those pursuing plasma therapy, isolation of neutralizing monoclonal antibodies, and determinants of immunity.